The World Bank and Non-Governmental Organizations - Nelson, P. author. aut Link
XIII, 235 p.
Keywords: This book assesses the World Bank's interaction with non-governmental organizations (NGOs) in projects, policy dialogue and elsewhere. Based on extensive project documents, public and private policy statements and interviews, the author identifies central organizational barriers to greater collaboration and accountability, and links these to the international political economy of the World Bank. The author suggests guidelines for judging organizational change in the World Bank, reviews opportunities and dangers for NGOs in relating with major aid donors, and discusses agenda and strategy.